Revisiting preview search at isoluminance: new onsets are not necessary for the preview advantage. - Braithwaite, J; Humphreys, G; Watson, D; Hulleman, J (2005)
It has been argued that search performance under preview conditions relies on automatic capture by luminance onsets (Donk and Theeuwes, 2001). We present three experiments in which preview search was examined with both isoluminant and nonisoluminant items (e.g., as defined by luminance onsets). Experiment 1 provided evidence against the automatic capture of attention by onsets. Search benefited when onset previews were followed by new onset stimuli, as compared with a full-set baseline matched for the number of new onsets but in which half the distractors appeared simultaneously at isoluminance. Furthermore, both Experiments 1 and 2 established a preview advantage when isoluminant targets followed onset previews, when compared with appropriate full-set baselines. Experiment 3 replicated this result, while showing that the preview benefit was disrupted by dual-task interference. The data indicate that new onsets are not necessary to generate a preview advantage in search. We discuss the data in terms of search's benefiting from active inhibition of old onset-defined stimuli.